Technical Efficiency Analysis of Mini Purse Seine Fishing Unit in Sumenep District - Fatoni, Mohammad Ibrahim; Hanani, Nuhfil; Suhartini, Suhartini (HABITAT, 2017)
The nature of competition in each purse seine fishing unit leads to excess fishing capacity utilization. This study aimed to analyze factors affecting fishing capacity in the short term, knowing the level of efficiency at each purse seine fishing unit, and to analyze factors affecting technical inefficiency. This study was conducted in Sumenep, East Java. The method used was parametric inferential statistics. The method of nalysis in this study was SFA (Stochastic Frontier Analysis) and tobit model. The research results show that number of trip, amount of FADs used, and the number of crew operator operating purse seine are significant factors affecting fishing capacity, average level of technical efficiencyâs of fishing unit is 36%, and the factors that negatively influence the technical inefficiency is experience of captain and the status of ownership of the vessel while the the factors that positively influence is age of captain.